Leveraging Generative AI to Convert Web Learning Content into Open Educational Resources - Payen Jean Baptiste, Valérie; Psyché, Valéry; Demers, Geneviève; Kagorora, Faustin (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2025)
This contribution aims to present the different stages of a design thinking methodological approach (Brown, 2009), which consists in training and using the ChatGPT generative AI model to analyze the content of a course’s resources; extract and analyze the types of licenses used and the degrees of accessibility and openness of the resources; and assist in the process of transforming them into open educational resources. By focusing on this AI-assisted research method, we aspire to make it easier for educators and content developers to transform standard educational materials into open educational resources and present a practical case of generative AI orchestration, thus enriching digital education with AI.